Afghan Lecturers' Perception of Problem-Based Learning: A Case Study of Takhar University - Sayeed Naqibullah Orfan; Sayeed Asif Akramy; Abdul Qawi Noori; Aminuddin Hashemi (Halla Newcastle Education and Research Center, 2021)
The study investigated the lecturers' perceptions of problem-based learning (PBL); their attitudes towards PBL, their views of effects of PBL on the learning process and the factors for not employing PBL in their courses. A survey questionnaire was used to collect data from 40 randomly selected lecturers from Takhar University. Descriptive and inferential statistics were used to analyze the data. The findings showed that lecturers had strong positive attitudes towards PBL and they were interested in utilizing PBL in their teaching activities. They were aware of the effects of PBL on the learning process particularly students' learning. They believed that PBL could help students develop a variety of generic skills, e.g., communication and problem-solving skills, which are necessary for employment. However, most of the participants did not make use of PBL in their courses for various reasons such as large number of students in their classes and lack of appropriate infrastructure. The lecturers' gender, level of education and years of teaching experiences did not have any significant impact on their responses.